[Recenzja]: Włodzimierz Cieński, Od Lwowa do Teheranu. Wspomnienia duszpasterskie 1939-1942, oprac. Jacek Żurek, Katowice-Warszawa 2021, ss. 565, ISBN 978-83-9585-224-4 - Kiper, Daniel (Archiwa, Biblioteki i Muzea Kościelne, 2022)
Recenzja książki.